2008
DOI: 10.1038/bmt.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Reduced respiratory and skeletal muscle strength in survivors of sibling or unrelated donor hematopoietic stem cell transplantation

Abstract: We performed a retrospective analysis of muscle strength testing obtained following sibling or unrelated donor hematopoietic stem cell transplant (HSCT) between 1 January 1999 and 31 December 2003 in a cohort of 44 subjects at Tufts-New England Medical Center. Maximal inspiratory pressure (PI max ) was p80% predicted in 52% of subjects and p60% predicted in 20% of subjects; maximal expiratory pressure (PE max ) was p80% predicted in 88% of subjects and p60% predicted in 74% of subjects. Patients with a PI max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 27 publications
0
36
0
1
Order By: Relevance
“…In addition, we found that patients undergoing allo-HSCT had significantly low knee-extensor strength, BMI, and QOL compared to normative values. After HSCT, physical function and QOL are known to decrease due to various transplant complications such as GVHD and longterm clean-room confinement [5,9]. Therefore, our finding of decreased physical function and QOL before transplantation is considered important.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, we found that patients undergoing allo-HSCT had significantly low knee-extensor strength, BMI, and QOL compared to normative values. After HSCT, physical function and QOL are known to decrease due to various transplant complications such as GVHD and longterm clean-room confinement [5,9]. Therefore, our finding of decreased physical function and QOL before transplantation is considered important.…”
Section: Discussionmentioning
confidence: 93%
“…Graft vs. host disease (GVHD) is a complication of HSCT that includes nausea, emesis, and diarrhea, resulting in weakness [4]. These problems cause physical function to decline [5].…”
Section: Introductionmentioning
confidence: 99%
“…37 Our study demonstrates that a partly supervised exercise intervention that is initiated before HSCT and continues after discharge significantly reduced cancer-related fatigue and improves the secondary outcome parameters physical capacity, functioning, anger/ hostility, pain, and global distress, which are the most common and impairing adverse effects of allo-HSCT besides GVHD. [3][4][5] Recent studies have demonstrated that aerobic exercise is a potentially important intervention against cancer-related fatigue in general. 38 Our results extend these findings to the population of allo-HSCT patients, by use of a combined endurance and resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Besides graft-versus-host disease (GVHD) and infections, reduced physical performance and functioning, and particularly high levels of fatigue, negatively affect patients' quality of life (QoL). 3,4 Furthermore, affective disorders (depression, anxiety disorders) and somatic complications, such as diarrhea, nausea, and pain, cause distress to occur and reinforce each other. [5][6][7][8] This treatment-related burden can be severely debilitating and may limit reintegration into usual life activities.…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged treatment process leads to a decline in physical functioning due to the side effects of medical treatment [25,28]. Patients experience these stress symptoms even when the treatment is effective and they can be detrimental to the long-term success of HSCT.…”
Section: Introductionmentioning
confidence: 99%